Influence of Long-Term Soil Application of Sewage Sludge Rich in Phosphorus on Heavy Metals Bioavailability to Plants - de Melo, Wanderley José [UNESP]; Peruca de Melo, Gabriel Maurício; de Melo, Valéria Peruca (Taylor & Francis, 2018)
Sewage sludge presents risk to the environment and to human health, and therefore its correct disposal is a problem to be solved as quickly as possible. Its use in agriculture as a fertilizer or soil amendment has drawn the attention of producers because sewage sludge contains large concentrations of organic matter and plant nutrients such as nitrogen (N), phosphorus (P), zinc (Zn), and others. However, along with these welcome components, sewage sludge also contains in its composition potentially toxic trace elements and organic substances that are hazardous. Considering the benets and the risks of applying sewage sludge in agriculture, it is important to know the composition of the residue to be used, the soil properties where it will be used, and the climatic conditions. These factors are important because the trace elements available to plants will also move down the soil prole and contaminate underground water. It is important to prevent the entering of trace elements in the human food chain.